PTH-084 Nutritional Impact Of Anti-viral Therapy Of Genotype 1 Hepatitis C Patients. (9th June 2014) - Bennett, J; Young, K; Dundas, P; English, S; Mcleman, L; Vijayan, B; Fraser, A; Mukhopadhya, A
Abstract : Introduction: Hepatitis C Virus (HCV) is a leading cause of chronic hepatitis and liver cirrhosis, with an estimated 170 million patients infected worldwide. The, UKmost common genotype of HCV is Genotype 1. For many years, the 'Standard of Care' has been prolonged therapy with the combination of Polyethylene glycol interferon-α and Ribavirin for one year. The recent approval of drugs such as Telaprevir and Boceprevir has restructured treatment for genotype 1 HCV infection, both for previously treated or treatment-naïve patients. Specific dietary intake is warranted for adequate absorption of the protease inhibitors and this has led to a structured dietary advice being given to patients. We wanted to compare the nutritional impact of antiviral therapy in two groups of patients who underwent either dual or triple therapy. Methods: Treatment of hepatitis C patients at Aberdeen Royal Infirmary is undertaken by Hepatology specialist nurses who review these patients at designated time intervals. At each of these clinic visits the MUST score (Malnutrition Universal Screening Tool) is recorded in addition to the weight and BMI of the patient. Any patient who has a MUST score of 2 is referred for specialist dietetic input, which is also available at the clinic. At 4 weekly intervals, the HAD score for anxiety and depression is also recorded for all patients. Results: A total of 73 patients with Genotype 1 underwent therapy in the year 2012–2013, including 25 patients with dual therapy of PEG-IFN and Ribavirin and 48 patients on triple therapy of PEG-IFN, Ribavirin and Telaprevir. There was no statistical difference in the initial weight, BMI and MUST scores of these two groups of patients. The mean weight fell from 89.6 ± 17.9 kg to 83.7 ± 15.6 kg by the end of treatment in the dual therapy group with a parallel fall in BMI from 30.7 ± 5.4 to 28.8 ± 4.6 kg/m 2 . However, in the triple therapy group, the mean weight increased from 82.2 ± 30.5 kg to 82.7 ± 26.0 kg and a stable BMI from 26.4 ± 9.5 to 26.2 ± 8.3 kg/m 2 . Dietary referral and intervention was needed in 7/25 patients on dual therapy (28%) as opposed to 7/48 patients on triple therapy (14.6%) (p = 0.23) Conclusion: Weight reduction is a significant problem in patients undergoing dual therapy for hepatitis C as opposed to those undergoing triple therapy. Referral to the dietician was needed in a larger proportion of cases undergoing standard of care though it did not reach statistical significance. Dietary advice given with respect to protease inhibitors may have had a significant effect in combating the ill effects of the standard treatment of patients with Genotype 1 HCV infection. This specific advice should be extrapolated to all patients undergoing anti-viral treatment. Disclosure of Interest: None Declared.